Technology Structural Optimisation of a Subsoiler: Structural Optimisation of a Subsoiler (Biological Sciences - PJSIR, 2010)
An experimental study of a subsoiler, used for deep tillage in agricultural fields, was carried out to determine its maximum draft force. The working conditions of the subsoiler were simulated three-dimensionally. The simulation showed that a structural optimisation can be generated on a subsoiler framework body for reducing the weight. New design parameters of the framework were defined and finite element analysis gave an optimised redesign for the subsoiler with the framework weight reduced by approximately 27.62%.